Does Delayed Cord Clamping Improve Long-Term (≥4 Months) Neurodevelopment in Term Babies? A Systematic Review and a Meta-Analysis of Randomized Clinical Trials - Serena Xodo; Serena Xodo; Luigi Xodo; Giovanni Baccarini; Lorenza Driul; Lorenza Driul; Ambrogio P. Londero; Ambrogio P. Londero (Frontiers Media S.A., 2021)
Background: Recently, the literature suggested that placental transfusion facilitated by delayed cord clamping (DCC), besides having benefits on hematological parameters, might improve the infants' brain development.Objective: The present review primarily evaluates the Ages and Stages Questionnaire (ASQ) total score mean difference (MD) at long-term follow-up (≥4 months) comparing DCC (>90 or >180 s) to early cord clamping (ECC). Secondary aims consisted of evaluating the ASQ domains' MD and the results obtained from other methods adopted to evaluate the infants' neurodevelopment.Methods: MEDLINE, Scopus, Cochrane, and ClinicalTrials.gov databases were searched (up to 2nd November 2020) for systematic review and meta-analysis. All randomized controlled trials (RCTs) of term singleton gestations received DCC or ECC. Multiple pregnancies, pre-term delivery, non-randomized studies, and articles in languages other than English were excluded. The included studies were assessed for bias and quality. ASQ data were pooled stratified by time to follow up.Results: This meta-analysis of 4 articles from 3 RCTs includes 765 infants with four-month follow-up and 672 with 12 months follow-up. Primary aim (ASQ total score) pooled analysis was possible only for 12 months follow-up, and no differences were found between DCC and ECC (MD 1.1; CI 95: −5.1; 7.3). DCC approach significantly improves infants' communication domains (MD 0.6; CI 95: 0.1; 1.1) and personal-social assessed (MD 1.0; CI 95: 0.3; 1.6) through ASQ at 12 months follow-up. Surprisingly, the four-month ASQ personal social domain (MD −1.6; CI 95: −2.8; −0.4) seems to be significantly lower in the DCC group than in the ECC group.Conclusions: DCC, a simple, non-interventional, and cost-effective approach, might improve the long-term infants' neurological outcome. Single-blinding and limited studies number were the main limitations. Further research should be performed to confirm these observations, ideally with RCTs adopting standard methods to assess infants' neurodevelopment.Trial registration: NCT01245296, NCT01581489, NCT02222805, NCT01620008, IRCT201702066807N19, and NCT02727517